Pregnancies in women with Turner syndrome: a retrospective multicentre UK study. (4th January 2022) - Cauldwell, M; Steer, PJ; Adamson, D; Alexander, C; Allen, L; Bhagra, C; Bolger, A; Bonner, S; Calanchini, M; Carroll, A; Casey, R; Curtis, S; et al.
Abstract : Objective: To determine the characteristics and outcomes of pregnancy in women with Turner syndrome. Design: Retrospective 20‐year cohort study (2000–20). Setting: Sixteen tertiary referral maternity units in the UK. Population or sample: A total of 81 women with Turner syndrome who became pregnant. Methods: Retrospective chart analysis. Main outcome measures: Mode of conception, pregnancy outcomes. Results: We obtained data on 127 pregnancies in 81 women with a Turner phenotype. All non‐spontaneous pregnancies (54/127; 42.5%) were by egg donation. Only 9/31 (29%) pregnancies in women with karyotype 45, X were spontaneous, compared with 53/66 (80.3%) pregnancies in women with mosaic karyotype 45, X/46, XX ( P  < 0.0001). Women with mosaic karyotype 45, X/46, XX were younger at first pregnancy by 5.5–8.5 years compared with other Turner syndrome karyotype groups ( P  < 0.001), and more likely to have a spontaneous menarche (75.8% versus 50% or less, P  = 0.008). There were 17 miscarriages, three terminations of pregnancy, two stillbirths and 105 live births. Two women had aortic dissection (2.5%); both were 45, X karyotype with bicuspid aortic valves and ovum donation pregnancies, one died. Another woman had an aortic root replacement within 6 months of delivery. Ten of 106 (9.4%) births with gestational age data were preterm and 22/96 (22.9%) singleton infants with birthweight/gestational age data weighed less than the tenth centile. The caesarean section rate was 72/107 (67.3%). In only 73/127 (57.4%) pregnancies was there documentation of cardiovascular imaging within the 24 months before conceiving. Conclusions: Pregnancy in women with Turner syndrome is associated with major maternal cardiovascular risks; these women deserve thorough cardiovascular assessment and counselling before assisted or spontaneous pregnancy managed by a specialist team. Tweetable abstract: Pregnancy in women with Turner syndrome is associated with an increased risk of aortic dissection. Tweetable abstract: Pregnancy in women with Turner syndrome is associated with an increased risk of aortic dissection. Linked article This article is commented on by RN Brown, pp. 804 in this issue. To view this minicommentary visit https://doi.org/10.1111/1471-0528.17022 .